Mr. Jefferson's lost cause : land, farmers, slavery, and the Louisiana Purchase - Kennedy, Roger G. (New York : Oxford University Press, 2003)
Thomas Jefferson advocated a republic of small farmers--free and independent yeomen. And yet as president he presided over a massive expansion of the slaveholding plantation system--particularly with the Louisiana Purchase--squeezing the yeomanry to the fringes and to less desirable farmland. Now Roger Kennedy conducts an eye-opening examination of that gap between Jefferson's stated aspirations and what actually happened. Kennedy reveals how the Louisiana Purchase had a major impact on land use and the growth of slavery. He examines the great financial interests that beat down slavery's many opponents in the South itself (Native Americans, African Americans, Appalachian farmers, and conscientious opponents of slavery). He describes how slaveholders' cash crops (first tobacco, then cotton) sickened the soil and how the planters moved from one desolated tract to the next. Soon the dominant culture of the entire region--from Maryland to Florida, from Carolina to Texas--was that of owners and slaves producing staple crops for international markets. The earth itself was impoverished, in many places beyond redemption. None of this, Kennedy argues, was inevitable. He focuses on the character, ideas, and ambitions of Thomas Jefferson to show how he and other Southerners struggled with the moral dilemmas presented by the presence of Indian farmers on land they coveted, by the enslavement of their workforce, by the betrayal of their stated hopes, and by the manifest damage being done to the earth itself.
Resistance to the plantation system. Chapter 9. McGillivray -- Mixed people and mixed motives -- Indian statehood -- McGillivray's nationality -- McGillivray and Washington -- Chapter 10. Resisters, assisters, and lost causes -- Scots, Blacks, and Seminoles -- The firm -- The valences shift -- William Augustus Bowles : the second act -- Bowles and Ellicott -- "Execute him on the spot" -- The fox is run to earth -- Chapter 11. The firm steps forward -- Deerskins, rum, and land -- Indian yeomen and Governor Sargent's lost cause -- Yankee yeomen -- Chapter 12. Jeffersonian strategy and Jeffersonian agents -- Jefferson and Wilkinson -- Wilkinson's clients -- The firm adapts and collects -- Wilkinson, Forbes, and Dearborn -- Debt for land -- The accounts of Silas Dinsmoor -- The firm wraps things up -- Andrew Jackson takes charge, with some help from Benjamin Hawkins -- Agents of the master organism : assistants to the plantation system. Chapter 13. Fulwar Skipwith in context -- Skipwith the Jeffersonian -- Toussaint's yeoman republic -- The career of Fulwar Skipwith -- The quasi war and spoliation -- James Monroe's first mission to France -- Skipwith, the Livingstons, and Louisiana cotton -- The chancellor, indolent maroons, and Thomas Sumter -- Mister Sumter is shocked -- The third article -- Skipwith and the Floridas -- Consul Skipwith goes to jail -- Chapter 14. Destiny by intention -- The adventures of George Mathews -- War, commerce, and race -- Assisters and resisters -- The green flag of Florida -- Chapter 15. Louisiana and another class of Virginians -- The third opportunity reconsidered -- The Hillhouse debates -- Chapter 16. The Virginians of Louisiana decide the future of the land -- Out of the hills -- The Kemper outrage -- 1809-1810 -- Skipwith and Randolph -- Complexities in Baton Rouge -- Skipwith at bay -- Haiti again -- Skipwith's Florida -- Epilogue. The Jeffersonian legacy : The Civil War and the Homestead Act -- Statesmanship and self-deception -- Final thoughts -- The economics of land use -- Appendix. Another stream -- Jefferson, Madison, Adam Smith, and the Chesapeake cities -- The Romans, armed occupation, and the Homestead Act -- Jefferson and the Ordinances of 1784 and 1787-89 -- Debt and land -- Jefferson's Doctrine of usufruct -- Tribes, land, and Ireland -- Creeks, Seminoles, and numbers -- The Livingstons and West Florida -- The Claiborne-Clark duel -- Fulwar Skipwith and Andrew Jackson.
Includes bibliographical references (pages 312-335) and index.
Keywords: Louisiana Purchase; Jefferson, Thomas, -- 1743-1826 -- Influence; United States -- Territorial expansion; United States -- Politics and government -- 1775-1783.; United States -- Politics and government -- 1783-1865.; Slavery -- United States -- Extension to the territories; Plantation owners -- Political activity -- United States -- History; Family farms -- United States -- History; Land settlement -- Political aspects -- United States -- History; Jefferson, Thomas, -- 1743-1826; Family farms; Influence (Literary, artistic, etc.); Land settlement -- Political aspects; Louisiana Purchase; Plantation owners -- Political activity; Political science; Slavery -- Extension to the territories; Territorial expansion; United States; Grondbezit; Slavernij; Louisiana Purchase; Jefferson, Thomas; USA -- Regierung; Sklaverei; Geschichte 1775-1865.; Louisiana Purchase; 1775 - 1865; History